2021
DOI: 10.1186/s12909-021-02539-5
|View full text |Cite
|
Sign up to set email alerts
|

A thematic network for factors affecting the choice of specialty education by medical students: a scoping study in low-and middle-income countries

Abstract: Background Medical specialty selection is a complex phenomenon that can affect the performance of health systems, community health, and physicians’ lives. It is essential to identify the key factors influencing the choice of specialty for evidence-based policymaking. This scoping review aimed to provide a comprehensive map of evidence regarding the factors influencing the choice of specialty by medical students (MS) in low-and middle-income countries (LMICs) and also to determine knowledge gaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…The number and type of specialists required is also based on the existing number of specialists in each discipline and their spatial distribution [ 2 , 4 ]. This has resulted in an ever-growing body of literature on medical specialist career choices among medical students and medical graduates [ 5 , 6 ]. Yet, to date, to the best of our knowledge only two other studies have reported psychometric properties of questionnaires used to study the motivators for selected medical specialist career choices [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The number and type of specialists required is also based on the existing number of specialists in each discipline and their spatial distribution [ 2 , 4 ]. This has resulted in an ever-growing body of literature on medical specialist career choices among medical students and medical graduates [ 5 , 6 ]. Yet, to date, to the best of our knowledge only two other studies have reported psychometric properties of questionnaires used to study the motivators for selected medical specialist career choices [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The items to be included as probes were discussed among the authors (AN and CTS) until a consensus was reached. Additional items to be included as probes were also derived from published systematic reviews and individual studies reported from Malaysia [ 5 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main themes that emerged from the scoping review were used to develop a topic guide for the qualitative study. The findings of the review study are published in a separate report [ 36 ]. In the second stage, 41 in-depth interviews were conducted with medical students (N: 12), junior doctors (N: 11), and medical residents (N: 18) to identify the most important determinants of specialty selection in Iran.…”
Section: Methodsmentioning
confidence: 99%